Assessment of the Degree of Relatedness of Some Inbred Lines Created at ARDS Turda - Andrei Varga; Roxana Elena Călugăr; Carmen Vana; Loredana Ceclan; Ionuț Racz; Nicolae Tritean (Agronomy, 2023)
Knowledge of relatedness among maize elite breeding genotypes is useful in planning crosses for hybrid and inbred line improvement and assigning them into heterotic groups. This study investigated phenotypic and genetic similarities or diversities between 7 flint inbred lines (of common origin) adapted to the early maize growing regions created at ARDS Turda-Romania. They were studied for per se traits and in two crossing systems: a diallel crossing system, resulting in 21 hybrids and a cyclic system using four testers, thus resulting in 28 maize hybrids. Both parental inbred lines and hybrids were evaluated for several traits over three years. The level of relatedness/diversity was determined by various methods, grouped into: phenotypic methods and genetic methods. Similarities were identified between certain lines and a degree of differentiation between others. The analysis of the hybrid combinations from the diallel crossings between the seven sister lines highlighted the TD236 inbred line as the only one that differs genetically from the other. Following the analysis of the data obtained in the cyclic system, some inbred lines can be sources of favorable traits: TD236 and TD233 for yield, ear weight, grain/ear weight; TD233 and TD234 for the number of kernels/row, TD237 for plant breaking resistance.